2017
DOI: 10.3390/ohbm1010003
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress in Hearing Loss

Abstract: Abstract:The endoplasmic reticulum (ER) plays important roles in coordinating protein biosynthesis and secretion in the cell. Accumulation of misfolded and/or unfolded proteins in the ER causes ER stress and the so-called unfolded protein response (UPR). The UPR alleviates ER stress through blocking protein synthesis and activating expression of chaperone genes, whereas prolonged UPR could induce cell death. Recent research has showed that ER stress and UPR are involved in hearing loss. Accordingly, animal exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 110 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, it has been shown that reduced expression of WFS1 results in reduced expression of NKA β subunit [202]. It has been reported that WFS1 expression is induced by protein kinase RNA-like ER kinase (PERK) [216]. Recent in vivo studies examining the role of genetics in response to F − exposure found that chronic F − exposure inhibits the expression of PERK [217].…”
Section: Molecular Mechanisms By Which Fluoride Inhibits Na+ K+-amentioning
confidence: 99%
“…Furthermore, it has been shown that reduced expression of WFS1 results in reduced expression of NKA β subunit [202]. It has been reported that WFS1 expression is induced by protein kinase RNA-like ER kinase (PERK) [216]. Recent in vivo studies examining the role of genetics in response to F − exposure found that chronic F − exposure inhibits the expression of PERK [217].…”
Section: Molecular Mechanisms By Which Fluoride Inhibits Na+ K+-amentioning
confidence: 99%